Entrepreneurial Success Model for Creative MSMEs in West Java: Implications for Entrepreneurship Education - Rizaldi, Fikri Mohamad; Suryana, Suryana; Mulyadi, Hari; Dian Herdiana Utama , Rd.; Pradana, Mahir (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: To develop and test an entrepreneurial success model for creative micro, small, and medium enterprises (MSMEs) in West Java, Indonesia, by examining five entrepreneur-level factors entrepreneurial self-efficacy, entrepreneurial alertness, entrepreneurial creativity, opportunity recognition, and entrepreneurial orientation and to derive implications for entrepreneurship education. Methods: A quantitative explanatory survey of 432 creative-industry MSME owners was conducted (January–March 2025). Data were analyzed using PLS-SEM (SmartPLS 4) to estimate direct and mediating effects. The analysis followed standard procedures for outer/inner model evaluation (indicator loadings ≥0.70 where retained; reliability and HTMT satisfied) and bootstrapping (5,000 resamples) for path significance. Results: All five factors contributed significantly to entrepreneurial success. Self-efficacy, alertness, and entrepreneurial orientation showed positive direct effects, while creativity mediated the effects of self-efficacy and alertness, and opportunity recognition mediated the effects of alertness and entrepreneurial orientation. The structural model explained R² = 0.716 (71.6%) of the variance in success (creativity R² = 0.644; opportunity recognition R² = 0.584), indicating substantial explanatory power. Novelty: The study shows that entrepreneurial traits influence success primarily through the mediating mechanisms of creativity and opportunity recognition. This trait–mechanism coupling provides a clearer explanation of how entrepreneur-level factors translate into performance and offers actionable guidance for entrepreneurship education targeting these mediating capabilities.